Implementation of Arduino in the Control Panel Room Temperature Monitoring and Control System - Awan Setiawan (SEAN Institute, 2023)
A web-based air temperature and humidity monitoring system is a proactive strategy to prevent material damage in the component manufacturing process. Critical temperature and humidity conditions affect the integrity and quality of semiconductor components, both from physical and functional aspects. Controlling air conditions is essential for optimizing components on the control panel. With the machine operating at maximum capacity or under heavy load, this system utilizes a DHT11 sensor and Nodemcu v.3 microcontroller equipped with an esp8266 wifi module to send data to the server via the internet. Through temperature monitoring and control devices, information can be accessed and monitored from other devices. All measurement data is stored in a database for analysis of air conditions in the panel control area. This analysis information is useful for maintenance and improvement of the cooling system in the control panel room.